AN ANALYSIS OF CULTURAL CONTENT OF ENGLISH TEXTBOOK FOR TENTH GRADE SENIOR HIGH SCHOOL - Sania, Mita; Cahyani, Fibria; Priastuti, Dyah Nugraheny (Journal of Education and Research, 2023)
This study aimed to discover aspects of cultural content and describe how the culture is represented in English textbooks using descriptive qualitative method with content analysis. The data were collected from the English textbook "Bahasa Inggris," designed for the first tenth-grade Senior High School semester based on the revised 2013 curriculum. The result shows that it is mainly presented through Universality across cultures in categories of culture (39,6%). The target culture (14,9%) has the slightest intention in this textbook. Next, most of the culture with the most minor parts is Perspective (10%). Meanwhile, the sense of culture was dominated by aesthetic sense (42,7%). Semantic sense (10%) has the slightest intention in this textbook. In this textbook, many cultures are not specific to any particular culture or country. In addition, this research also found an unbalanced quantity of data on this cultural aspect.